Two snakes from eastern Australia (Serpentes: Elapidae); a revised concept of Antaioserpens warro (De Vis) and a redescription of A. albiceps (Boulenger) - Couper, Patrick J.; Peck, Stephen R.; Emery, Jon-Paul; Keogh, J. Scott (Zootaxa, 2016)
Antaioserpens warro sensu lato is known from two populations, one in north-eastern Queensland (Qld), the other from south central Qld. Morphological and genetic assessments demonstrate that these widely separated populations represent two species. A re-examination of museum specimens and the type descriptions show that the name A. warro (De Vis) has been erroneously applied to the north-eastern Qld species. The type specimen of A. warro, from the Gladstone district in south-east Qld, is badly faded but the colour pattern as described by De Vis (1884a) is consistent with that of recently collected specimens from south central Qld and it is this species to which the name applies. The earliest available name for the species from north-eastern Qld is A. albiceps (Boulenger, 1898). Both A. warro and A. albiceps are redescribed herein.